2020
DOI: 10.1002/adom.202000187
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Enhancing Photoluminescence Quantum Efficiency and Optical Gain of Polyfluorene via Backbone Intercalation of 2,5‐Dimethyl‐1,4‐Phenylene

Abstract: Simultaneous enhancement of photoluminescence quantum efficiency (PLQE) and optical gain in semiconducting polymer films is desirable for optically‐ or electrically‐pumped organic solid‐state lasers. In this work, a simple self‐dilution effect is achieved by introducing a small amount (≈10% by weight) of 2,5‐dimethyl‐1,4‐phenylene (DP) units in the backbone of poly(9,9‐dioctylfluorene) (PFO). The resulting copolymers, compared with PFO (PLQE 39%), exhibit a significantly increased PLQE (66%) while keeping simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…[ 13 ] Broad fluorescence spectra allow, on the other hand, for broadband amplification. [ 14,15 ] In addition, the photoluminescence (PL) spectra can be tailored by backbone modification, e.g., by controlling the conjugation length [ 16 ] or by the introduction of electron‐donor or electron‐acceptor groups, [ 17 ] in contrast to inorganic semiconductors where the emitting wavelengths are restricted to lattice‐matching requirements. The efficiency of solid‐state light emission is quantified through the photoluminescence quantum efficiency (PLQE), which stands for the ratio between the number of emitted and absorbed photons.…”
Section: Fundamental Photophysics Of Organic Gain Mediummentioning
confidence: 99%
See 2 more Smart Citations
“…[ 13 ] Broad fluorescence spectra allow, on the other hand, for broadband amplification. [ 14,15 ] In addition, the photoluminescence (PL) spectra can be tailored by backbone modification, e.g., by controlling the conjugation length [ 16 ] or by the introduction of electron‐donor or electron‐acceptor groups, [ 17 ] in contrast to inorganic semiconductors where the emitting wavelengths are restricted to lattice‐matching requirements. The efficiency of solid‐state light emission is quantified through the photoluminescence quantum efficiency (PLQE), which stands for the ratio between the number of emitted and absorbed photons.…”
Section: Fundamental Photophysics Of Organic Gain Mediummentioning
confidence: 99%
“…The efficiency of solid‐state light emission is quantified through the photoluminescence quantum efficiency (PLQE), which stands for the ratio between the number of emitted and absorbed photons. [ 18 ] Considerable efforts have been devoted to further increase the PLQE of organic semiconductor thin films to achieve high gain and low‐threshold organic lasers [14a,19] . The major strategy to achieve this goal is to localize excitons and minimize the intermolecular interactions, so that dynamic and static luminescence quenching is reduced.…”
Section: Fundamental Photophysics Of Organic Gain Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…Organic π-conjugated materials exhibit very interesting features as active media in laser devices. They show high room-temperature photoluminescence quantum efficiencies (PLQE) [ 89 , 90 ] which translates into large stimulated emission (SE) cross-section values and their photoluminescence (PL) spectra can be tuned through chemical functionalization [ 91 ]. Moreover, organic lasers can be processed by cost-effective solution-based methods [ 92 ], they have capabilities to confine and guide light due to their elevated refractive indexes [ 93 ] and they possess unique mechanical properties (flexibility and light weight) leading to new potential market niches for organic laser devices.…”
Section: Organic Solid Lasersmentioning
confidence: 99%
“…The separation of semiconducting polymers from each other (dilution) does not allow for good electronic transport, but other work [ 21 ] showed that, by mixing different polyfluorenes, it was possible to have films of semiconducting polymers with both optical gain and excellent charge transport properties. Further, alternative, approaches include mimicking the effects of dilution by adding a small amount of dimethyl phenylene into polyfluorene chains [ 22 ] or by the supramolecular separation of chains by threading cyclodextrin rings around the conjugated polymer to create polyrotaxanes [ 23 ].…”
Section: Introductionmentioning
confidence: 99%